2014
DOI: 10.1016/j.jval.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Osteoporosis on High-Cost Chronic Diseases

Abstract: The burden of osteoporosis in patients with CD is significant, particularly for patients with newly diagnosed osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
0
9
0
3
Order By: Relevance
“…A possible explanation for this is the influence of musculoskeletal diseases on coexisting chronic diseases. Thayer et al reported that an incident osteoporosis increased the all‐cause total costs of patients with a coexisting disease by 66% to 91% (Thayer et al ., ). Further relevant observations supporting our explanation have been reported by Osiri and Sattayasomboon, who found that the all‐cause and rheumatoid arthritis specific total costs of rheumatoid arthritis patients were raised by 100% (all‐cause total costs) and 25% (rheumatoid arthritis specific total costs), respectively, by the existence of comorbid conditions (Osiri and Sattayasomboon, ).…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation for this is the influence of musculoskeletal diseases on coexisting chronic diseases. Thayer et al reported that an incident osteoporosis increased the all‐cause total costs of patients with a coexisting disease by 66% to 91% (Thayer et al ., ). Further relevant observations supporting our explanation have been reported by Osiri and Sattayasomboon, who found that the all‐cause and rheumatoid arthritis specific total costs of rheumatoid arthritis patients were raised by 100% (all‐cause total costs) and 25% (rheumatoid arthritis specific total costs), respectively, by the existence of comorbid conditions (Osiri and Sattayasomboon, ).…”
Section: Discussionmentioning
confidence: 97%
“…It has been estimated that 87% of all fractures in the elderly are the result of a fall and 5–10% of all falls result in a fracture [ 466 , 467 , 468 ]. Among 494,160 patients aged ≥50 years with OP, 9% had only OP, while the rest had also chronic diseases, including CVD (54%), DM (8%), depression (4%), COPD (1%), with two or more diseases in 24% [ 469 ]; the HPI status in this study has not been reported.…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 98%
“…Because smoking is a major risk factor for chronic diseases, which may be seriously aggravated by concurrent osteoporosis (9), better understanding the interaction of smoking and calcium intake on bone health would be very important. However, large-scale epidemiological replications of this effect modification are lacking.…”
mentioning
confidence: 99%